2019
DOI: 10.1186/s12955-019-1200-3
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in chronic hepatitis B patients is significant and associates with autonomic dysfunction

Abstract: Background Fatigue is an important clinical finding in patients with chronic hepatitis virus infection. However, studies assessing fatigue in patients with chronic hepatitis B (CHB) are very limited. This study aimed to quantify the severity of fatigue in patients with CHB, to determine whether perceived fatigue reflects impairment of functional ability, and to explore potential causes. Methods A total of 133 patients with histologically proven CHB and 59 community cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Fatigue appears to be a very common presentation of the disease both at the acute and post infectious stages of COVID-19 [25]. It was reported to be directly related to autonomic dysfunction in some of the reported studies [26] and the relationship of fatigue with autonomic dysfunction in some other neurological diseases such as multiple sclerosis [27], Parkinson's disease [28], sleep disorders [29] and chronic hepatitis [30] is also well known. Although Towsend et al reported that there was no difference in terms of autonomic dysfunction symptoms between patients with fatigue and non-fatigue [31], our results show that the presence of fatigue at the acute stage of SARS-CoV-2 infection increases the risk of autonomic dysfunction by 2.2 folds at the post COVID phase.…”
Section: Discussionmentioning
confidence: 98%
“…Fatigue appears to be a very common presentation of the disease both at the acute and post infectious stages of COVID-19 [25]. It was reported to be directly related to autonomic dysfunction in some of the reported studies [26] and the relationship of fatigue with autonomic dysfunction in some other neurological diseases such as multiple sclerosis [27], Parkinson's disease [28], sleep disorders [29] and chronic hepatitis [30] is also well known. Although Towsend et al reported that there was no difference in terms of autonomic dysfunction symptoms between patients with fatigue and non-fatigue [31], our results show that the presence of fatigue at the acute stage of SARS-CoV-2 infection increases the risk of autonomic dysfunction by 2.2 folds at the post COVID phase.…”
Section: Discussionmentioning
confidence: 98%
“…Lethargy was a clinical indicator of the presence of hepatic cytolysis in our study. Patients with acute viral hepatitis may show a high degree of fatigue and lethargy, which may be related to the severity of liver disease [ 39 , 40 ]. The direct association of cytolysis with vomiting and dehydration identified by us has not been clearly described to date, especially for cases of HAdV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic viral hepatitis can also cause long-term brain dysfunction, which significantly worsens the quality of life and may even persist after the elimination of the virus (Dirks et al, 2017). With chronic HBV-infection, the quality of life may also be worsened due to the appearance of fatigue, cognitive impairment and sleep disorders (Wang et al, 2019).…”
Section: Risk Factors Of Cognitive Impairmentmentioning
confidence: 99%
“…Cortisol, IL-6, and TNF-α were associated with levels of perceived fatigue, especially cognitive impairment in patients with HBV infection. The characteristic of fatigue in patients with chronic liver disease was noted as central fatigue (Wang et al, 2019). Some studies have shown that fatigue is a true and specific sign of HDV-infection that negatively affects the quality of life, while a significant proportion of fatigue in HBV is associated with the presence of autonomic dysfunction (Ekerfors et al, 2019).…”
Section: Chronic Fatiguementioning
confidence: 99%